Learning Tools an Interactive Audio-Visual on The Book English for Specific Purposes as Supporting English Language Teaching for Students - Kasuya, Igast Layli; Oktavianti, Vitasoma (Journal of Blended and Technical Education, 2024)
Objective: The objective of this research is to design and test an audio-visual-based ESP book as an interactive learning media that addresses the specific language needs of students in professional or academic contexts. This study aims to develop a product that enhances learning through multimedia integration, improving the effectiveness of ESP teaching. Research Design & Methods: This research follows a product design approach, including several stages:(1) Identifying the learning plan,(2) Determining learning objectives aligned with competencies,(3) Compiling materials and embedding learning video barcodes that students can scan and access, and (4) Designing the book to enhance its appeal. The product was then tested in a real classroom environment, with pretest and posttest assessments used to evaluate its effectiveness and suitability. Findings: The findings show that the implementation of audio-visual ESP books is proven to be effective in improving learning outcomes and student engagement, so educational institutions should consider adopting multimedia materials with interactive features to enrich ESP learning. Implications & Recommendations: The study suggests that he integration of audio-visual media in ESP textbooks effectively improves student engagement and learning outcomes, so educational institutions are advised to adopt multimedia materials with interactive features to meet the specific needs of learners in the professional field. Contribution & Value Added: This study shows that audio-visual media is effective in improving language acquisition, thus offering a practical solution and innovative model for the development of interactive ESP teaching materials in the future.